Large array device characteristics improvements. (October 2021) - Huang, Shao-Chang; Li, Ching-Ho; Liao, Chih-Cherng; Chen, Li-Fan; Chen, Chun-Chih; Hsu, Kai-Chieh; Lin, Gong-Kai; Lin, Chih-Hsuan; Lee, Jian-Hsing; Kao, Yu-Yung; Chen, Ke-Horng
Abstract: Large array devices are often used for big current driving capabilities in power electronic integrated circuit (IC) applications. Since these structures have big sizes, typical electrostatic discharge protection methodologies cannot be applied in such kind of IC. Otherwise, IC will become too huge to marketing. In this paper, a novel signal control switching architecture for adding large array devices' ESD performances is proposed. Only a little layout area is increased, but a huge electrostatic discharge robustness improvement can be obtained. Moreover, electrical safe operation area characteristics of large array devices are also improved very much with this new scheme. This study is processed in 0.15 μm Bipolar CMOS DMOS (BCD) with silicide technologies. Highlights: This is a very big study which can provide a good solution for pure 5 V power IC applications. The research is based on our previous paper, published in 2018 MR. Finally, it can be applied very well in the industry.